Long-term impact of urgent secondary prevention after transient ischemic attack and minor stroke: ten-year follow-up of the EXPRESS study - Luengo-Fernandez, R; Li, L; Silver, L; Gutnikov, S; Beddows, NC; Rothwell, PM (AHA Journals, 2021)
Background and Purpose: Urgent assessment aimed at reducing stroke risk after transient ischemic attack or minor stroke is cost-effective over the short-term. However, it is unclear if the short-term impact is lost on long-term follow-up, with recurrent events being delayed rather than prevented. By 10-year follow-up of the EXPRESS study (Early Use of Existing Preventive Strategies for Stroke), previously showing urgent assessment reduced 90-day stroke risk by 80%, we determined whether that early benefit was still evident long-term for stroke risk, disability, and costs.